The subjective wellbeing profile of the 'pretiree' demographic: A cross-sectional study. (April 2018) - Pasco, Julie A.; Holloway, Kara L.; Stuart, Amanda L.; Williams, Lana J.; Brennan-Olsen, Sharon L.; Berk, Michael
Highlights: The term 'pretirees' refers to an emerging demographic interposed between the latter stages of working life and old age. Nearly half of the pretirees in this study described their overall quality of life as being very good, with substantial numbers rating it as good. Nonetheless, clusters of low scores for quality of life and their associated lifestyle patterns were apparent. For all domains, habitual physical activity was the behaviour most consistently associated with greater scores for quality of life. There are opportunities for lifestyle interventions without which many pretirees might enter old age at risk of diminished wellbeing in at least one of the quality-of-life domains. Abstract: Objectives: Pretirees are a demographic interposed between the latter stages of working life and old age. We aimed to characterise subjective wellbeing and lifestyle behaviours for individuals aged in their late-fifties and sixties. Study design: Cross-sectional study of 233 men and 229 women aged 55–69 yr from the Geelong Osteoporosis Study. Main outcome measures: Subjective wellbeing assessed using the World Health Organization Quality of Life questionnaire (WHOQOL-BREF, Australia). Scores below published population norms for Australia for WHOQOL domains (physical, psychological, social, environmental) were considered low. Results: For men, low WHOQOL scores were evident for 78 (33.5%) of participants regarding physical health, 94 (40.3%) for psychological wellbeing, 89 (38.2%) for social relationships, and 99 (42.5%) for the environment; the respective figures for women were 110 (48.0%), 124 (54.1%), 84 (36.7%), and 95 (41.5%). While there were few smokers (men 10.8%; women 6.5%), 42.5% of men and 17.7% of women exceeded recommended alcohol levels; 6.4% of men and 15.2% of women met the recommendation to consume each day at least two portions of fruit and five of vegetables. In multivariable models, being active was consistently associated with high WHOQOL scores, and low socioeconomic status with low WHOQOL scores. Pain and polypharmacy were associated with increased likelihood of poor scores for physical health, living with a partner increased the likelihood of good social relationships, and body mass index, employment, sleep, and alcohol and fruit/vegetable intakes were associated with WHOQOL scores in at least one domain. Conclusions: There is an opportunity for targeting health promotion to pretirees, particularly in socially disadvantaged regions, in order to optimise transition into old age. Our data highlight lifestyle interventions without which many pretirees might progress to old age at increased risk of diminished wellbeing.